Wearable technologies in the fashion value ecosystem: a conceptual model - Rosiane Serrano; Larissa Fortunati; Daniel Pacheco Lacerda (Innovation & Management Review, 2022)
Purpose - The fashion sector is complex. It involves multiple actors with distinct and potentially conflicting interests, forming a value ecosystem. Thus, knowing the interested parties and belonging to the fashion sector may be a means to promote technological innovation, such as products with wearables. The purpose of this paper to identify the participants of the fashion ecosystem from the perspective of wearable technologies and develop a conceptual model. Design/methodology/approach - The present work aims to identify the participants (actors) and develop a conceptual model of the fashion ecosystem from the perspective of wearable technologies. The systematic literature review is the recommended method to qualitatively analyze documents and identify the interested parties (actors) in the fashion sector in order to design the proposed conceptual model. Findings - From the studies, the conceptual model of the fashion value ecosystem was designed, and the wearable product was considered its core business. The studies identified addressed ecosystems of fashion value in general but not specific to wearable products and their relations with other complementary industries. Research limitations/implications - The model was designed using secondary data only. Its validation is relevant through interviews with experts. Originality/value - In terms of relevance, when conducting a systematic literature review, there were no studies that included wearable technologies in the fashion ecosystems discussed and their relations with other industries. The topic of wearables is an emerging subject that needs further research aiming to insert this technology in productive sectors.
Keywords: 650; Fashion ecosystem; Fashion sector; Systematic literature review; Wearable technologies